Dynamic analysis of historic railway bridges in Poland in the context of adjusting them to PENDOLINO trains - Grębowski, Karol; Zielińska, Monika (Zielona Góra: Uniwersytet Zielonogórski)
The article presents the dynamic analysis of the historic railway bridge in Tczew as an example of the usefulness of such type of bridge for high-speed trains. The model of the bridge and the simulation of rolling stock passage was performed in SOFISTIK program. The scope of work includes experimental studies, the solution of the problem concerning the correct solution features of the dynamic model which takes into account the dependencies between the bridge, track and rolling - stock (RBT).
Keywords: dynamic analysis; modal analysis; historic bridges; high-speed trains